Toward an easier indigocarmine chromoendoscopy - Barret, Maximilien (World J Gastrointest Endosc, 2015)
Indigocarmine chromoendoscopy has been proven to improve the detection of colonic lesions during screening colonoscopy, and is associated with increased adenoma detection rates. Furthermore, it is commonly used to help in the delineation and characterization of colorectal neoplasms. However, it usually requires the use of a spraying catheter that decreases the suction capacity of the endoscope, and is time- consuming. Herein, we report on the feasibility of indigo carmine chromoendoscopy during colonoscopy without using a spraying catheter, with the dye being administered through the air/water channel of the endoscope. Since the suction channel remains free, the air can be exsufflated and the staining then applies uniformly onto the colonic walls with the excess indigocarmine dye being immediately eliminated. In our experience with various types of colonoscopes and cap-assisted colonoscopy, this procedure makes indigocarmine chromoendoscopy much easier and quicker to perform, and might save the use of a spray catheter.